2008
DOI: 10.1099/jmm.0.2008/004671-0
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of Bartonella species from rodents in Taiwan including a strain closely related to ‘Bartonella rochalimae’ from Rattus norvegicus

Abstract: An increasing number of Bartonella species originally isolated from small mammals have been identified as emerging human pathogens. During an investigation of Bartonella infection in rodent populations carried out in Taiwan in 2006, a total of 58 rodents were tested. It was determined that 10.3 % (6/58) of the animals were Bartonella bacteraemic. After PCR/RFLP analysis, four isolates were identified as Bartonella elizabethae and one isolate as Bartonella tribocorum. However, there was one specific isolate wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
29
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 24 publications
4
29
0
Order By: Relevance
“…Bartonella sp. 1-1C, which was previously isolated from R. norvegicus in Taiwan, 9 was detected in fleas in the present study. In Taiwan, fleas and lice may be efficient vectors for infection of small mammal hosts with several Bartonella species.…”
Section: Discussionsupporting
confidence: 66%
“…Bartonella sp. 1-1C, which was previously isolated from R. norvegicus in Taiwan, 9 was detected in fleas in the present study. In Taiwan, fleas and lice may be efficient vectors for infection of small mammal hosts with several Bartonella species.…”
Section: Discussionsupporting
confidence: 66%
“…In this study, specificity of some bartonellae for host animals was observed (Table 3). The R. rattus brunneusculus rats carried almost all the rat-origin Bartonella species detected in this study, except B. rochalimae, which was isolated recently from R. norvegicus in Taiwan (19). In our study, S. murinus shrews harbored mostly B. queenslandensis.…”
supporting
confidence: 60%
“…Previously, several reports were made on the occurrence of bartonellae in rodents and other small mammals in Asian countries, including Bangladesh (3), China (28), Indonesia (27), Japan (16), Laos (1), Taiwan (19), and Thailand (2,7,24). Recently, Bai et al (3) reported that 63.2% of B. bengalensis, 32.3% of R. rattus, and 42.9% S. murinus animals collected in Dhaka, Bangladesh, were infected with Bartonella, and the isolates from these animals were genetically related to Bartonella isolates found in America and Europe.…”
mentioning
confidence: 99%
“…Color images available online at www.liebertpub.com/vbz vinsonii , B. doshiae, B. grahamii, and B. taylorii (Birtles et al 1995), B. tribocorum (Heller et al 1998), B. vinsonii subsp. arupensis (Welch et al 1999), B. birtlesii (Bermond et al 2000), B. washoensis , B. phoceensis and B. rattimassiliensis (Gundi et al 2004), B. rochalimae (Lin et al 2008), B. tamiae , B. rattaustraliani, B. queenslandensis, and B. coopersplainsensis (Gundi et al 2009), B. japonica and B. silvatica , and B. jaculi, B. callosciuri, B. pachyuromydis, and B. acomydis (Sato et al 2013). Other Bartonella isolated from rodents have been proposed as new species or subspecies, including Candidatus Bartonella washoensis subsp.…”
Section: Figmentioning
confidence: 99%